Indications for Cesarean Sections at ≥34 Weeks Among Nulliparous Women and Differential Composite Maternal and Neonatal Morbidity. Issue 4 (December 2015) - Chauhan, S.P.; Beydoun, H.; Hammad, I.A.; Babbar, S.; Hill, J.B.; Mlynarczyk, M.; D'Alton, M.E.; Abuhamad, A.Z.; Vintzileos, A.M.; Ananth, C.V.
Abstract : ( BJOG . 2014;121(11):1395–1402)